2013
DOI: 10.1007/s11187-013-9473-0
|View full text |Cite
|
Sign up to set email alerts
|

Top management teams and the performance of entrepreneurial firms

Abstract: This article examines why some entrepreneurial firms succeed while others do not. The focal explanation is top management teams, including several studies that address when and how top management teams are likely to influence entrepreneurial firm performance. There are several insights.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 42 publications
2
65
0
1
Order By: Relevance
“…Resources which are embedded in the entrepreneur's relationship networks involve management skills in terms of the ability to coordinate all these resources (Hernández-Carrión et al 2017). Top managers of effective entrepreneurial firms are creating and maintaining alliances, developing products, selecting employees (Eisenhardt 2013), and employing top management styles (Covin and Slevin 1989). As such, they are strategic resources for the firm.…”
Section: Coordinative Capabilities Hypothesesmentioning
confidence: 99%
“…Resources which are embedded in the entrepreneur's relationship networks involve management skills in terms of the ability to coordinate all these resources (Hernández-Carrión et al 2017). Top managers of effective entrepreneurial firms are creating and maintaining alliances, developing products, selecting employees (Eisenhardt 2013), and employing top management styles (Covin and Slevin 1989). As such, they are strategic resources for the firm.…”
Section: Coordinative Capabilities Hypothesesmentioning
confidence: 99%
“…The articles reviewed in this section demonstrate that entrepreneurial team cognition facilitates decision‐effectiveness. By relying on ‘simple rules’ heuristics to perform significant activities such as new product development and internationalization (Eisenhardt ), entrepreneurial teams become more efficient. Eventually, these simple cognitive rules residing in the team can become the strategy of the firms.…”
Section: How Does Entrepreneurial Team Cognition Interact With Inputsmentioning
confidence: 99%
“…; West ). However, 40% of new ventures fail within the first year (Dimov and De Clercq ; Timmons ), and more than 60% of these failures are ascribed to problems with the entrepreneurial team (Eisenhardt ; Gorman and Sahlman ; Kaplan and Strömberg ). Research shows that the way in which entrepreneurial team members work together plays an important role in determining venture outcomes (Chowdhury ; Ensley and Pearce ; Ensley et al .…”
Section: Introductionmentioning
confidence: 99%
“…In the entrepreneurship and management literature it has generally been suggested that the heterogeneity of the management team's capabilities reflected in different education and professional backgrounds matters for growth (Cooper and Bruno 1977;Eisenhardt and Schoonhoven 1990;Eisenhardt 2013) because of the synergistic gains that may arise (Colombo and Grilli 2005). A certain degree of cognitive heterogeneity in the management team may stimulate organizational learning and broaden the venture's strategic perspectives, thus enhancing its growth potentials (Cooper and Bruno 1977;Eisenhardt and Schoonhoven 1990).…”
Section: General Human Capital and Growthmentioning
confidence: 99%